Tele-immersion - Jayanthila Devi (International Journal of Informatics and Communication Technology (IJ-ICT), 2016)
Tele-immersion is an advanced form of virtual reality that will allow users in different places to interact in real time in a shared simulated environment. Tele-immersion is a technology to be implemented with Internet that will enable users in different geographic locations to come together in a simulated environment to interact. Users will feel like they are actually looking, talking, and meeting with each other face-to-face in the same room.This technology causes users to feel as if they were in the same room. The tele-immersion technology uses a "tele-cubicle" which is equipped with large screens, scanners, sensors, and cameras. The tele-cubicles are linked together in real-time so that they form one larger cubicle. Through the virtual environment, participants are able to interact with other group members. Also, virtual objects and data can be passed through the walls between participants, and placed on the shared table in the middle for viewing.